The influence of return on assets and return on equity on company value asset - Cahya, Kamilah; Yusuf, Furtasan Ali; Kenedi, Kenedi (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the effect of Return on Assets and Return on Equity on firm value in automotive sector issuers listed on the Indonesia Stock Exchange during the 2020–2024 period. Profitability is viewed as a fundamental factor influencing market valuation and investor confidence, particularly in the automotive sector, which experienced significant pressure during the COVID-19 pandemic and the challenges of post-pandemic economic recovery. The research method employed a quantitative approach using secondary data in the form of financial reports and annual stock prices. The sample was determined through purposive sampling of automotive companies consistently listed on the IDX throughout the study period. Firm value was measured by the Price-to-Book Value (PBV) ratio, while the independent variables were ROA and ROE. Data analysis was performed using multiple linear regression with the classical assumption test to ensure model sphericity.The results of the hypothesis testing indicate that ROA and ROE simultaneously have a significant effect on firm value (p < 0.05). Partially, ROA has a positive and significant effect, indicating that efficient asset utilization directly increases firm value. Meanwhile, ROE also had a positive effect, but with a lower level of significance, indicating that return on equity also supports increased firm value, although it does not influence ROA.